Characteristics of Acupuncture Intervention for Chemotherapy-induced Peripheral Neuropathy Prevention: A Scoping Review of Clinical Trials - Alice Feng; Mingxiao Yang; Weidong Lu; Wanqing Iris Zhi; Ting Bao (Journal of Acupuncture Research)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common and debilitating condition among people with cancer receiving neurotoxic chemotherapy. Acupuncture demonstrates potential to prevent CIPN; however, there is limited pertinent data to guide protocols. This scoping review summarizes characteristics of acupuncture interventions in clinical trials evaluating the efficacy of acupuncture in preventing CIPN. Three eligible trials that included 102 participants receiving scheduled acupuncture to prevent CIPN during active chemotherapy were analyzed. These studies featured local and segmental acupoint selections with manual and electrical needling. Acupuncture paradigms were aligned with chemotherapy schedules from the initiation or presence of clinically bothersome CIPN to prevent symptoms from developing or worsening, respectively. Despite significant differences in needling techniques, therapeutic paradigms, and efficacy data, local and segmental acupoint selection is important in current clinical trials to prevent CIPN during active chemotherapy. Future studies should establish standardized acupuncture protocols through expert opinions and multidisciplinary collaboration for clinical validation.